The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s12652-016-0387-y
|View full text |Cite
|
Sign up to set email alerts
|

Internet of things for remote elderly monitoring: a study from user-centered perspective

Abstract: Improvements in life expectancy achieved by technological advancements in the recent decades have increased the proportion of elderly people. Frailty of old age, susceptibility to diseases, and impairments are inevitable issues that these senior adults need to deal with in daily life. Recently, there has been an increasing demand on developing elderly care services utilizing novel technologies, with the aim of providing independent living. Internet of things (IoT), as an advanced paradigm to connect physical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 169 publications
(62 citation statements)
references
References 81 publications
0
62
0
Order By: Relevance
“…There are additional challenges to using technology to support ageing in place, including low rates of adoption by older people the cause of which has been explained as poor interface design, issues of privacy and trust (Yusif et al 2016) economic barriers and educational barriers (Wang et al 2016;Satariano et al 2014). A number of studies have proposed that future IoT development will require a more user centred and co-creative design approach (Azimi 2017;Gkouskos and Burgos 2017;Greenhalgh et al 2015;van Hoof et al 2011;Beringer et al 2011) and age appropriate designs (Pietzrak et al 2014). In addition to these considerations, more evaluation of IoT systems in the home of older people is needed (Peek et al 2014;Reeder et al 2013)).…”
Section: Technology and Ageing In Placementioning
confidence: 99%
“…There are additional challenges to using technology to support ageing in place, including low rates of adoption by older people the cause of which has been explained as poor interface design, issues of privacy and trust (Yusif et al 2016) economic barriers and educational barriers (Wang et al 2016;Satariano et al 2014). A number of studies have proposed that future IoT development will require a more user centred and co-creative design approach (Azimi 2017;Gkouskos and Burgos 2017;Greenhalgh et al 2015;van Hoof et al 2011;Beringer et al 2011) and age appropriate designs (Pietzrak et al 2014). In addition to these considerations, more evaluation of IoT systems in the home of older people is needed (Peek et al 2014;Reeder et al 2013)).…”
Section: Technology and Ageing In Placementioning
confidence: 99%
“…Not only does remote health monitoring improve the quality of life of elderly patients, detects and notifies caregivers and providers of emergencies, reduces nursing care needs and hospital stays (e.g. health care cost reduction), it can predict and track disease processes such as heart attacks [28].…”
Section: The Internet Of Things and Disease Predictionmentioning
confidence: 99%
“…AAL and IoT healthcare related researches as well seems to be more focused on the assessment of the health conditions of the people under monitoring, their behavior (Eisa and Moreira 2017), the adherence to medical treatments (Roy et al 2017), patients' empowerment toward a more conscious healthy lifestyle (Grace et al 2017), or improving their self-sufficiency (Poncela et al 2019). Moreover, most of the studies reported in literature are targeted to the adult and elderly population (Azimi et al 2017), while very few studies foster the effects of smart environments or smart objects on children. A recent PubMed search 1 returned only one publication relevant in the area of pediatric rehabilitation (PR), describing a study where a small smart device has been attached to objects transforming them into computer simple mouse controllers (Szturm et al 2014).…”
Section: Introductionmentioning
confidence: 99%